Do espaço: uma interpretação fenomenológico-existencial a partir de Ser e tempo, de Heidegger - Morais, Maria Lucivane de Oliveira (2018)
This dissertation aims to analyze how the philosophy of Martin Heidegger brings real contribution to the thinking that considers space from the phenomenological-existential bases. His work is in direct conflict with the traditional understanding brought by regional ontologies and empirical sciences (especially the Geography that defines it by means of physical dimensions, by the way it is used by the man who inhabits it, attributing to it uses and values ). Although in the course of his work the philosopher recognizes the coherence of such definitions, his contribution focuses on showing that space is to be understood primarily as a constitutive experience of human existence in the face of its being-there situation (Dasein) . The methodology adopted was based on bibliographical research in Being and Time (1927), in commentators and other authors, allowing to present the considerations of this dissertation in two parts. In the first one, important concepts appear that allowed to situate the proposed study in relation to Being and time, understanding the Heideggerian project and the necessary course so that it was possible to put the question for the being, or rather, for the sense of being that was trivialized by tradition, as well as the subsidies necessary for an appropriated understanding of space. In the second part, we discussed how space was treated in the light of the understandings made possible by Heidegger's existential phenomenology. For this, it was necessary a reconstruction of the concept of space, objectively treated by the regional ontologies, especially, by the Geography that took it for itself when separating itself from the Philosophy in the course of century XIX when it was constituted like autonomous science, however, still requires aid of philosophers to weave their conceptual bases, which justifies the elaboration of this dissertation in which the important contributions of Heidegger were presented. Among the results obtained, we can emphasize that being-there is an open project whose only determination is its possibility of being. Space, while spatiality is a constitutive moment of being-there, being experienced phenomenally, opening itself to the multiple possibilities of being, that is, it is the field of play of being-in-the-world that has always been abruptly launched , without there being determinations, but possibilities to execute its existential project and to delineate the very meaning of its existence. Space is regarded as constitutive of the world; however, being-there and world can not be understood as two distinct entities, as if they were one within the other, as proposed in Geography, but as a single ontological unit that is clearly expressed in the term being-in-the-world. It is concluded, therefore, that before we think of a merely utilitarian space, integrated into a globalized network and / or configured by capital, it is necessary to recognize that it will be in existentially experienced ("lived") space that the being-there is understood , in the average everyday life "appears" along with other beings-there and intramundane beings, establishing certain behaviors in relation to those who come to meet them, appropriating themselves ontologically of the world and constituting new fields of meaning for their being.